1632 Va. Acts 198, Act 45 - (:unkn) unknown (General Publisher, 1632)
All men that are fitting to bear arms, shall bring their pieces to the church upon pain for every offence, if the default be in the master, to pay 2lb of tobacco, to be disposed by the church-wardens, who shall levy it by distress, and the servants shall be punished [ ] commander.
--
Keywords: REQUIRED POSSESSION